Patterns as basis for immersivity across the arts: a practice-led hypothesis - Jalhed, Hedvig (Frontiers in Psychology, 2025)
This article introduces the pattern theory of immersivity (PTI), a practice-led theoretical framework stemming from the hypothesis that a reorientation of the understanding of immersive art is needed, away from technological sophistication or sensory excess and toward the psychological mechanisms underlying imaginative engagement, regardless of artform or combination of media. The theory posits that immersivity—the capacity of an artwork to induce immersion—is primarily a function of patterned information structures that stimulate aspects of superior pattern processing (SPP). Immersion is reconceptualised as a process of cognitive filling-in, in which motifs that remain partially concealed elicit fantasies. A distinction is made between immersive perception and immersive performance, each articulated across three graduated levels, culminating in a peak immersive state. This pan-artistic model, formalised as the ORFEUS model, offers artists a tentative tool for designing and analysing the prerequisites for immersive experiences through strategic use of fragmentation, ambiguity, and indirect information. The theory underscores that immersivity is seldom a property of entire artworks, but rather a quality embedded in specific elements that provoke psychological engagement. Ultimately, PTI provides a refined vocabulary and a methodological approach for immersive artmaking in all media; one that integrates artistic know-how with knowledge about the deep structures of human cognition.